Implementation of BPOM Regulation No. 8 of 2020 Concerning Online Drug Distribution at 4 Pharmacies in Purworejo Regency, Indonesia - Aminudin; Jason Merari Peranginangin; Wiwin Herdwiani (HM Publisher, 2023)
The high number of internet users has an impact on the development of trade transaction models from conventional to electronic or online, known as e-commerce. The web-based or e-commerce business action plan in Indonesian regulations is called trading through electronic systems (PMSE). This study aimed to find out the implementation of BPOM regulation No 8 of 2020 concerning online drug distribution in 4 pharmacies in Purworejo Regency, Indonesia. This research is an observational study with a qualitative approach using information-gathering techniques through perception directly and meetings with several sources or witnesses related to this check. At the data analysis stage, the results of the interviews will be used as material for analyzed thematically by looking at and connecting with the problem formulation and research purposes. Interview data were analyzed using NVIVO 12 pro software. The implementation of BPOM Regulation No. 8 of 2020 related to the circulation of drugs distributed online in 4 pharmacies in Purworejo Regency has been running with a percentage of 79.55% in accordance with and 20.45% not in accordance with existing regulations. The implementation of BPOM Regulation No. 8 of 2020 concerning the Circulation of Drugs Distributed Online in pharmacies in Purworejo Regency has a significant impact on the supervision and safety of drug circulation through online platforms or e-commerce. In conclusion, based on the provisions contained in BPOM Regulation No. 8 of 2020 related to the circulation of drugs distributed online, most of the regulations have been implemented in the 4 pharmacies but improvements are still needed in the media used.